2022
DOI: 10.53730/ijhs.v6ns2.7972
|View full text |Cite
|
Sign up to set email alerts
|

Association of vitamin-D with hypothyroidism in adult female patients in north Indian population

Abstract: Background: Thyroid disorder is found to be most commonly occurring endocrine disorder in females. Thyroid hormones have an imperative position in metabolic methods in human body, and several physiological and pathological stimuli are known to influence thyroid metabolism. The increased incidence of hypovitaminosis D was diagnosed in population with hypothyroidism. Objective: To check the relation of Vitamin D in adult female patients diagnosed with hypothyroidism. Method: We recruited 60 patients and divided … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
1
0
0
Order By: Relevance
“…Most of the (65%) hypothyroid patients were belonged to obese category (BMI>25) found in the current study, most of them were moderate obesity (35.4%), our finding was concordance with the Yadav V et al [19] In our study maximum number of patients (78.1%) was belonged to upper-middle socio-economic status and most of them (65.8%) residing in urban areas, constant finding were reported by Sethi, et al [20] and Krishna JG et al [21]. Present study analysed clinical profile of all hypothyroidism patients, we have found that the most common presenting symptoms were weakness (85.8%), weight gain (69.2%), Facial irritability (57.9%), facial puffiness (47.1%) and menstrual Irregularity (45.4%), similar finding also observed by Manoj k Choudhary et al [22], and Shetty et al [23] On clinical examination commonly observed sign are weight gain (81.3%), pedal edema (47.1%), dry skin (28.3%), depression (27.5%), pallor (23.7%), and bradycardia (20.4%), accordance to other studies like: Dixit R et al [24] and Ravindra Kumar, et al [25], whereas Kumar et al [26] reported edema, dry skin and tachycardia was the predominant sign found in hypothyroidism patients. Present study found cold intolerance was reported in 16.2% cases, accordance with the Babu MG et al [27], .reported 16.6% cold intolerance in their study Infertility cases was found in 14.6% of hypothyroidism patient in the present study, concordance to the Fauzia Imtiaz et al [28], so all hypothyroid patients always worked up for infertility.…”
Section: Discussionsupporting
confidence: 84%
“…Most of the (65%) hypothyroid patients were belonged to obese category (BMI>25) found in the current study, most of them were moderate obesity (35.4%), our finding was concordance with the Yadav V et al [19] In our study maximum number of patients (78.1%) was belonged to upper-middle socio-economic status and most of them (65.8%) residing in urban areas, constant finding were reported by Sethi, et al [20] and Krishna JG et al [21]. Present study analysed clinical profile of all hypothyroidism patients, we have found that the most common presenting symptoms were weakness (85.8%), weight gain (69.2%), Facial irritability (57.9%), facial puffiness (47.1%) and menstrual Irregularity (45.4%), similar finding also observed by Manoj k Choudhary et al [22], and Shetty et al [23] On clinical examination commonly observed sign are weight gain (81.3%), pedal edema (47.1%), dry skin (28.3%), depression (27.5%), pallor (23.7%), and bradycardia (20.4%), accordance to other studies like: Dixit R et al [24] and Ravindra Kumar, et al [25], whereas Kumar et al [26] reported edema, dry skin and tachycardia was the predominant sign found in hypothyroidism patients. Present study found cold intolerance was reported in 16.2% cases, accordance with the Babu MG et al [27], .reported 16.6% cold intolerance in their study Infertility cases was found in 14.6% of hypothyroidism patient in the present study, concordance to the Fauzia Imtiaz et al [28], so all hypothyroid patients always worked up for infertility.…”
Section: Discussionsupporting
confidence: 84%